2022
DOI: 10.1111/1751-7915.14142
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol: Endophytic bacteria could be crucial to fight soft rot disease in the rare medicinal herb, Anoectochilus roxburghii

Abstract: Microbial destabilization induced by pathogen infection has severely affected plant quality and output, such as Anoectochilus roxburghii, an economically important herb. Soft rot is the main disease that occurs during A. roxburghii culturing. However, the key members of pathogens and their interplay with non-detrimental microorganisms in diseased plants remain largely unsolved.Here, by utilizing a molecular ecological network approach, the interactions within bacterial communities in endophytic compartments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Co-occurrence network analysis (CNA) is a more powerful tool than simple diversity analysis, which was more commonly used, for studying host-microbe and microbe-microbe interactions ( 24 , 25 ). CNA can specifically identify the core microbiomes (i.e., the hub microbes) that influence community structure ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Co-occurrence network analysis (CNA) is a more powerful tool than simple diversity analysis, which was more commonly used, for studying host-microbe and microbe-microbe interactions ( 24 , 25 ). CNA can specifically identify the core microbiomes (i.e., the hub microbes) that influence community structure ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…The plant microbiome is an essential determinant of plant health and productivity 12 . The microbiome of medicinal plants may directly impact the metabolism of the host, and thus could in uence the e cacy of herbal medicine 13 . Two main stratagems have been proposed on microbes in uence the production and accumulation of bioactive ingredients in medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…To exploit the potential of plant‐associated microorganisms as biostimulants, biofertilizers, and biopesticides, a deeper knowledge needs to be gained in the assembly of the plant microbial community, plant microbiome responses to biotic and abiotic stresses, as well as the complex interactions between plant‐associated microorganisms and between microbes and their plant hosts (Bazany et al, 2022 ; Compant et al, 2019 ; Rico‐Jiménez et al, 2022 ). Some of these aspects have been addressed in a recent study in Microbial Biotechnology where the authors found important differences in the microbial composition and diversity of healthy and diseased plants, providing evidences that specific native microbial members may assist the pythopathogens during the infection process (Xing et al, 2022 ).…”
mentioning
confidence: 99%